ULTRASONOGRAPHIC DIAGNOSIS AND MANAGEMENT OF HYDROMETRA IN GOATS - SRIDEVI, P; KULASEKAR, K; DEVANATHAN, T G; RANGASAMY, S (The Indian Journal of Animal Reproduction, 2011)
Ultrasonography, a reliable diagnostic tool for pseudopregnancy in goats.